Doença veno-linfática: alterações linfocintilográficas nas úlceras venosas - Silva, José Humberto [UNIFESP] (2009)
Background: The lymphatic system plays a relevant role in any type of peripheral edema. Lymphoscintigraphy is currently considered the primary test in the diagnosis of lymphatic disease of the lower limbs. Although there is an association between lymphatic edema and chronic venous ulcers, the physiopathology of such changes remains uncertain. Objective: To assess qualitative lymphoscintigraphic findings in patients with chronic venous ulcers of the lower limbs. Methods: Forty patients with unilateral chronic venous ulcer or scar were submitted to bilateral lymphoscintigraphy of the lower limbs. The sample was comprised of 25 women and 15 men, with a mean age of 53.7 years (28 to 79) and mean ulcer duration of 71.5 months (3 to 240 months). Lymphoscintigraphic parameters were qualitatively compared among three groups of lower limbs previously classified according to the clinical, etiologic, anatomic and pathologic classification (CEAP): I, limbs without clinical signs of venous disease or with telangiectasias and/or reticular veins (classes 0 and 1); II, limbs with varicose veins, edema and/or skin and subcutaneous alterations (classes 2, 3 and 4); III, lower limbs with ulcer and/or ulcer scars (classes 5 and 6). Results: There was a significant difference (p < 0.001) in the comparison of lymphoscintigraphic findings of the lower limbs with (group III - classes 5 and 6) and without ulcers/scars (groups I and II - classes 0, 1, 2, 3 and 4). There was also a significant difference (p < 0.001) in the comparison of groups according to the clinical CEAP classification: lymphoscintigraphic abnormalities were present in 72.5% in group III (classes 5 and 6), in 30.8% in group II (classes 2, 3 and 4), and in 7.1% in group I (classes 0 and 1). There was a statistically significant difference between group III and the other groups with regard to radiotracer retention, inguinal adenomegaly and dermal reflux. There was no significance as to the parameters popliteal lymph node and collateral circulation. Conclusion: The more severe the venous chronic stasis, the more lymphoscintigraphic abnormalities were observed, corroborating the association between venous and lymphatic disease and between chronic venous stasis and secondary lymphedema.